The Gendered Impact of Social Norms on Financial Access and Capital Misallocation - Arti Grover; Mariana Viollaz (Institute of Labor Economics (IZA), 2025)
This paper provides evidence on the nature of financial constraints faced by women entrepreneurs, especially in contexts of stringent social norms. Using micro-data from the World Bank Enterprise Surveys for 61 countries, the analysis shows that formal firms managed by women do not face credit constraints on the extensive margin. They are equally likely to apply for credit as their male counterparts and experience lower rates of credit rejection, with a higher likelihood of opening credit lines. However, on the intensive margin, firms managed by women receive lower credit amounts, indicating signs of credit constraints. This disparity in access to credit cannot be explained by gender differences in risk profiles, profitability, or productivity. However, firms managed by women have lower sales per worker, suggesting challenges in accessing product and labor markets. The paper finds suggestive evidence of capital misallocation based on gender, particularly in countries with more restrictive gender and cultural norms. Firms managed by women demonstrate a 15 percent higher average return on capital compared to firms managed by men, indicating the potential benefits of increased access to credit for women-led businesses. These findings emphasize the importance of addressing gender-specific constraints to accessing finance and promoting gender-inclusive policies to enhance firm growth and reduce capital misallocation.
Keywords: D22; D24; J16; 330; firms; credit; capital misallocation; gender; social and cultural norms